Fenton Oxidation using Easily Recoverable Catalyst of Magnetite (Fe3O4) as an Efficient Approach to Treatment of Rhodamine B Dyeing Effluent in Traditional Fabrics Industry - Imam Prasetyo; Febry Akbar; Anindya Widi Prabandari; Teguh Ariyanto (ASEAN Journal on Science and Technology for Development, 2019)
A direct release of dye wastewater to a water environment without pre-treatment could cause negative impacts. To solve them, an effective method for degrading wastewater contaminants is needed. In this research, the Fenton reaction using Fe3O4 catalyst for removal of wastewater contaminants taken from a traditional fabrics industry was studied. For this purpose, reaction temperature was varied in the range of 27–90°C. Furthermore, catalyst concentration was also varied in the range of 2–6 g/L solution. The results showed that increasing both temperature and catalyst concentration will increase the performance of the Fenton reaction in degrading wastewater contaminants. The contaminant degradation was measured by detecting chemical oxygen demand and inspecting the color of wastewater. The highest reduction of color intensity was 98.96% at 90°C temperature and 2 g Fe3O4/L solution.